Pendampingan Magang dalam Rangka Meningkatkan Kompetensi Mahasiswa pada Pengadilan Agama Surabaya - Widia Ari Susanti; M. Sifa Fauzi Yulianis (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Internship is a learning process and or work practice for students to develop themselves and increase their knowledge about the world of work. This program functions to introduce the world of work to students, as well as improve their competence in the theories that students have learned in lectures to then be applied in the world of work. This internship is carried out by students at the Surabaya Religious Court. The activities carried out include providing consultations and making lawsuits/applications at the posbakum, providing information about court procedures in the information section, further processing lawsuits/applications registered in the registration section, mediating the parties in the case in the mediation room, and finally observing the course of the trial in the courtroom including conducting trial simulations.